Effects of Electroacupuncture at Zusanli and Quchi on Neurological Function Recovery in Rats with Cerebral Infarction - Jiangcong HONG; Yingzheng WANG; Guangwen WU; Yulong ZOU (康复学报)
Objective:To observe the effects of electroacupuncture at Zusanli and Quchi acupoints on focal ischemic brain injury in rats from the behavioral, histological and molecular levels, respectively, and to provide experimental evidence for the clinical application of electroacupuncture in the treatment of cerebral infarction.Methods:A total of 144 male Sprague Dawley(SD)rats weighing(250±30)g were selected and randomly divided into three groups: sham-operated group, electroacupuncture(EA)group and model group. The common carotid artery, internal carotid artery and external carotid artery of the rats in the sham-operated group were separated after anesthesia without ligation or thread insertion. In the EA and model groups, the middle cerebral artery occlusion(MCAO)models were achieved by Zea-Longa sutured-occluded method. According to Bederon and Longa scoring methods, simple neurobehavioral scoring was performed on the rats after the model was established. Rats with 0 and 4 scoring points were excluded. One day after the operation, the rats in the EA group were electroacupunctured at Zusanli and Quchi acupoints. The appropriate depth of needling was slight shaking of affected limbs in rats after electrification. Simulation parameters: dilatational wave, frequency of sparse wave 4 Hz and dense wave 20 Hz, pulse width 0.5 ms, output voltage 2 V, output current 0.5 mA, 20 min/(time·day).In the model group, except no acupuncture, the rest of the process was the same as that of the EA group. The changes in walking, hind limb standing and licking behaviors of the rats were observed with Homecage Scan monitoring system 1, 7 and 14 days after the cerebral ischemia reperfusion. The rats were also sacrificed 1, 7 or 14 days after operation, with the volume of cerebral infarction in rats determined by the 2, 3, 5-Triphenyl tetrazolium chloride(TTC)staining method. In addition, BrdU-positive cells, double positive cells of BrdU/DCX and double positive cells of BrdU/NeuN were used as markers of proliferation, migration and differentiation of neural stem cells, respectively. The proliferation, migration and differentiation of neural stem cells in rats were observed by double immunofluorescence staining at the 1st, 7th and 14th day after cerebral ischemia reperfusion of the rats.Results:1.No neurologic impairment was observed in the sham-operated group in the research. In the EA and model groups, the impairment was the severest one day after the operation, and the nerve function was recovered gradually as time went on, but it could not recover to the level of the sham-operated group until 14 days after the operation. In addition, there was no significant difference between the EA group and model group on the first day after the operation(P>0.05). The behavior scores of the rats in the EA group was higher than that of the model group(P<0.05)after 7 and 14 days.2.No TTC staining could be observed in the sham-operated group at all the three time points. The staining was the strongest one day after the cerebral ischemia reperfusion, and the staining range was reduced later. There was no significant difference in the volume of cerebral infarction between the EA group and model group at the first day after operation(P>0.05). The infarct sizes detected by TTC staining were smaller in the EA group than in the model group after 7 and 14 days(P<0.05).3. The BrdU-positive cells began to increase one day after the establishment of the MCAO model and reached the peak at the 7th day in the EA and model groups. At the 1st day, there was no significant difference in the population of BrdU-positive cells between the EA group and model group(P>0.05), however, at the 7th and 14th day, the population in the EA group increased more significantly compared with the model group(P<0.05). The double positive cells of BrdU/DCX increased significantly in the MCAO models at the 7th day, reaching the peak. The 1st day after MCAO modeling, no significant difference could be found in the population of BrdU/DCX positive cells between the EA group and model group(P>0.05), while, at the 7th and 14th day, the number of BrdU/DCX positive cells in the EA group was significantly higher than that in the model group(P<0.05). The population of BrdU/NeuN positive cells grew from the 7th day, and no significant difference was existed between the EA group and model group at the time points(P>0.05).Conclusion:Electroacupuncture at Zusanli and Quchi acupoints has been proved to improve the neurological function of rats with cerebral infarction and reduce the volume of cerebral infarction. Besides, it also improved the expression of DCX but not NeuN. Therefore, the electroacupuncture treatment can also promote the proliferation and migration of neural stem cells but not induce a great change in the differentiation.